Adropin a candidate diagnostic biomarker for cardiovascular disease in patients with chronic kidney disease - Maha Abd El Moneem Elfedawy; Samia Abd El Sadek Elsebai; Hend Mohamed Tawfik; Eman Refaat Youness; Moushira Zaki (Journal of Genetic Engineering and Biotechnology)
Background: Chronic kidney disease (CKD) is a chief worldwide health concern that has a substantial financial impact on health systems, high rates of mortality and morbidity as well as cardiovascular disease (CVD) is a major cause of mortality in this population. Adropin is a unique hormone encoded by the energy homeostasis-associated (Enho) gene. Aim of the work: We aimed to explore the efficacy of adropin as a diagnostic candidate biomarker for CVD in patients with CKD. Methods: This is prospective study was carried out on 60 patients (Pt) with CKD and 30 age and sex matched healthy control subjects. CKD Pt were classified according to the history of CVD into two groups: Group A, Pt without history (n = 32) and Group B, Pt with history (n = 28). Serum adropin, lipids and Hs-CRP were measured by ELISA kit. Echocardiography was also investigated. Receiver operator characteristic curve (ROC) was used to determine cut-off points of adropin. Negative predict value (NPV), negative predict value (NPV) and area under curve were detected. Results: There were abnormal ECGs in 78.6 % of CKD patients. Adropin was significantly decreased in Group B than Group A and control group. On the other hand, serum lipids and Hs-CRP were significantly increased in Group B than Group A and control group. ROC analysis revealed that serum adropin could be used to discriminate between patients with and without CVD history at a cutoff level of > 304 with 46.4 % sensitivity and 84.4 % specificity, 74.8 % PPV, 61.2 % NPV and AUC = 0.57. Moreover, between Group A and control at a cutoff level of < 410, with 93.8 % sensitivity, 86.7 % specificity, 87.6 % PPV and 93.3 % NPV and AUC = 0.97 as well as between Group B and control group at a cutoff level of < 416, with 57.1 % sensitivity, 83.3 % specificity, 77.4 % PPV and 66 % NPV and AUC = 0.65. Conclusion: Particularly in CKD patients, adropin may be a useful biomarker for predicting the onset of CVD. Adropin may represent a novel and useful blood marker for assessing systolic function and Spontaneous coronary artery dissection (SCAD).